Lessons for Hospital Autonomy : Implementation in Vietnam from International Experience - Vietnam Ministry of Health; Health Strategy and Policy Institute; World Bank; World Health Organization (World Bank, Washington, DC, 2017)
The Government of Vietnam sees hospital autonomy policy as important and consistent with current development trends in Vietnam. It is based on government policies as laid out in government Decree on financial autonomy of revenue-generating public service entities; and to 2006, it is replaced by decree on professional, organizational, human resource management and financial autonomy of revenue-generating and state budget-financed public service entities. These policies apply to public service entities in all sectors, including the health sector and hospitals. This policy is an important element of public administration reform in Vietnam, helping service entities survive and develop under the socialist-oriented market mechanism. It aims to help hospitals in fulfilling assigned professional tasks by allowing them to restructure their organization and staffing. The government has also allowed public service entities to mobilize private capital and joint ventures to organize activities and services responding to social and people's needs. This study will show that since the implementation of decrees, a number of improvements have been demonstrated within hospitals with respect to physical facilities, service provision, medical techniques, service quality and staff incomes, thus creating stability and satisfaction among hospital workers. But it also describes the international evidence that implementation of hospital autonomy comes with a risk of unintended outcomes driven by powerful financial incentives from the market place to increase revenue. These include supply induced demand, cost escalation, inappropriate care. There are some indications that such risks may be emerging in Vietnam as well, although these would need further research. Fortunately, there is also international evidence about policies that can mitigate such risks, and these are also described in this report. This report will inspire further studies and encourage policymakers to think about continuous improvement of policies.